Betaine Supplementation and Milk Production during Heat Stress in Crossbred Cows - Shankhpal, Sachin S; Waghela, Chanchal R; Sherasia, Pankaj L; Srivastava, Ajay K; Sridhar, V (Indian Journal of Animal Nutrition, 2018)
Present study was conducted to evaluate the effect of supplementing betaine on milk production in 20 early lactating (30-35 days in milk) crossbred cows (HF X Jersey) during hot summer months (April to July, 2018) in Anand district of Gujarat state. Cows yielding 18-20 kg milk per animal per day were divided into two groups of ten each, based on milk yield, fat% and stage of lactation. The animals in both the groups were fed basal diet, comprising of 9.0 kg concentrates, 25.0 kg green fodder and 3.5 kg dry fodder. In addition to basal diet, animals in experimental group were supplemented betaine hydrochloride @ 30 g/day and buffer @ 100 g per day for 90 days. The average temperature-humidity index was 71.78 and 78.12 at 09:00 and 14:00 hrs, respectively. Study revealed that betaine supplementation improved DMI and milk yield significantly (P